2004
DOI: 10.1097/00001813-200404000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of thymidylate synthase expression and its steady-state mRNA by oxaliplatin in colon cancer cells

Abstract: Recently, evidence has accumulated that weekly 24-h infusion of high-dose 5-fluorouracil (5-FU) with leucovorin (LV, folinic acid) biochemical modulation may improve the response rates compared with the bolus 5-FU regimens in colorectal cancer (CRC). Combining the infusional 5-FU/LV (iFL) regimens with oxaliplatin or irinotecan is widely adopted to further improve treatment efficacy. Either oxaliplatin-iFL or irinotecan-iFL may achieve an overall response rate of more than 50% in the first-line treatment. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
2
28
1
Order By: Relevance
“…Moreover, we also showed that TSGH cells could become more sensitive to 5-FU through gene silencing via TS-targeted siRNA method ( Figure 6B), which validated the important role of downregulated TS gene in rendering S3 cells more sensitive to 5-FU ( Figure 6C). Although the detailed mechanism for oxaliplatin-induced TS gene downregulation needs to be further elucidated, our result is concordant with two previous reports (Raymond et al, 2002;Yeh et al, 2004), which indicated that oxaliplatin could downregulate TS in cancer cells and thus potentiate the efficacy of 5-FU. As oxaliplatin and 5-FU have been shown to be highly synergistic not only in preclinical models (Raymond et al, 1997) but also in subsequent clinical trials (Rothenberg et al, 2003;Chao et al, 2004;Lordick et al, 2005;Schippinger et al, 2005;Cavanna et al, 2006), our data provide important information regarding why the combination of oxaliplatin and 5-FU results in better objective response than single use alone.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we also showed that TSGH cells could become more sensitive to 5-FU through gene silencing via TS-targeted siRNA method ( Figure 6B), which validated the important role of downregulated TS gene in rendering S3 cells more sensitive to 5-FU ( Figure 6C). Although the detailed mechanism for oxaliplatin-induced TS gene downregulation needs to be further elucidated, our result is concordant with two previous reports (Raymond et al, 2002;Yeh et al, 2004), which indicated that oxaliplatin could downregulate TS in cancer cells and thus potentiate the efficacy of 5-FU. As oxaliplatin and 5-FU have been shown to be highly synergistic not only in preclinical models (Raymond et al, 1997) but also in subsequent clinical trials (Rothenberg et al, 2003;Chao et al, 2004;Lordick et al, 2005;Schippinger et al, 2005;Cavanna et al, 2006), our data provide important information regarding why the combination of oxaliplatin and 5-FU results in better objective response than single use alone.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, evidence has accumulated that oxaliplatin treatment results in downregulation of TS expression, providing a possible explanation, although still speculative, for the higher response rate of the combination of oxaliplatin and FU, compared with oxaliplatin alone, in FU-resistant patients (Yeh et al, 2004). In addition, it has been shown that oxaliplatin remains highly cytotoxic in cells that overexpress TS.…”
Section: Discussionmentioning
confidence: 99%
“…6A). The ternary complex is an inactive form of TS, whereas the free form of TS is an active enzyme (27). Figure 6A shows that, whereas the expression of the free TS in untreated cells increased with time, quercetin inhibited free TS protein compared with the corresponding controls at all time points, with the 72-h treatment resulting in a 90% inhibition of free TS protein.…”
Section: Inhibition Of Ts Expressionmentioning
confidence: 98%
“…27. The lysates were sonicated and cleared by centrifugation at 14,000 g for 15 min at 4°C, and the supernatant (total cell lysate) was used or immediately stored at -80°C.…”
Section: Ts Western Blottingmentioning
confidence: 99%